Neurobehavioral evaluation of neonates with congenital heart disease: a cohort study. (10th May 2018) - Hogan, Whitnee J; Winter, Sarah; Pinto, Nelangi M; Weng, Cindy; Sheng, Xiaoming; Conradt, Elisabeth; Wood, Janine; Puchalski, Michael D; Tani, Lloyd Y; Miller, Thomas A
Abstract : Aim: To describe neurobehavioral patterns in neonates with congenital heart disease (CHD). Method: A cohort study describing neurobehavioral performance of neonates with CHD requiring cardiac surgery. The neonates were evaluated preoperatively and postoperatively with the Neonatal Intensive Care Unit Network Neurobehavioral Scale (NNNS) and scores were compared with published normative values. Clinical factors were obtained by chart review to assess their association with behavior. The CHD NNNS score pattern was compared with previously reported profiles in other high‐risk populations. Results: NNNS evaluations were completed on 67 neonates with CHD, resulting in 97 evaluations (50 preoperative, 47 postoperative). Compared with normative values, the cohort with CHD demonstrated decreased attention, regulation, asymmetry, stress, arousal, and excitability, along with increased non‐optimal reflexes, lethargy, and need for handling ( p <0.05 for all). Additional clinical factors had a minimal effect on the neurobehavioral pattern. Compared with previously published patterns in high‐risk neonates without CHD, the cohort with CHD demonstrated a unique pattern of behavior. Interpretation: Neonates with CHD demonstrate different neurobehavioral performance compared with typically developing neonates born at term as well as other high‐risk neonates. Our experience suggests there is a unique neonatal neurobehavioral pattern in the hospitalized population with CHD. Targeted neonatal neurobehavioral evaluations may be useful in developing specific therapies to improve neurodevelopmental outcomes in neonates with CHD. What this paper adds: Neonates with congenital heart disease demonstrate different neurobehavioral performance than typically developing neonates. Evaluation of neonatal neurobehavioral performance provides an opportunity to identify neurodevelopmental variability early. Identification of neurobehavioral performance variability allows targeted interactions and therapy. What this paper adds: Neonates with congenital heart disease demonstrate different neurobehavioral performance than typically developing neonates. Evaluation of neonatal neurobehavioral performance provides an opportunity to identify neurodevelopmental variability early. Identification of neurobehavioral performance variability allows targeted interactions and therapy. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations. This article is commented on by Mebius and Bos on pages1192–1193 of this issue.